The Economics of Health - Meyer, Donald J. (W.E. Upjohn Institute, 2016)
Donald J. Meyer leads a group of notable health economists who explore critical issues-and their economic impacts-facing the nation's healthcare system today. These include lifestyle choices and their health impacts, decisions on medical care and self-care, the fee-for-service payment model, disability and workers' compensation insurance claims, long-term care, and how various aspects of the Patient Protection and Affordable Care Act (ACA) impact the nation's healthcare system. Contributors include M. Kate Bundorf, Marcus Dillender, John H. Goddeeris, Donald J. Meyer, Edward C. Norton, and Charles E. Phelps.